2022
DOI: 10.1177/17562848221094214
|View full text |Cite
|
Sign up to set email alerts
|

The role of bacterial translocation in sepsis: a new target for therapy

Abstract: Sepsis is a leading cause of death in critically ill patients, primarily due to multiple organ failures. It is associated with a systemic inflammatory response that plays a role in the pathogenesis of the disease. Intestinal barrier dysfunction and bacterial translocation (BT) play pivotal roles in the pathogenesis of sepsis and associated organ failure. In this review, we describe recent advances in understanding the mechanisms by which the gut microbiome and BT contribute to the pathogenesis of sepsis. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 169 publications
(255 reference statements)
1
14
0
2
Order By: Relevance
“…Moreover, we also observed a pertinent number of CFU in liver, spleen and the lung of mice subject to LPS injection. As described previously by others, this finding is most likely to be explained by bacteremia resulting from an increased intestinal barrier permeability and bacterial translocation, which can be found in various systemic and inflammatory diseases and play an important role in the pathogenesis of sepsis induced organ failure [28,29].…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, we also observed a pertinent number of CFU in liver, spleen and the lung of mice subject to LPS injection. As described previously by others, this finding is most likely to be explained by bacteremia resulting from an increased intestinal barrier permeability and bacterial translocation, which can be found in various systemic and inflammatory diseases and play an important role in the pathogenesis of sepsis induced organ failure [28,29].…”
Section: Discussionsupporting
confidence: 56%
“…16 Our previous study first showed that many infiltrated neutrophils in the intestine of LPS-induced septic rats were activated to release NETs, which led to intestinal damage during sepsis. 7 Therefore, it is of great significance to identify…”
Section: Discussionmentioning
confidence: 99%
“…16 Our previous study first showed that many infiltrated neutrophils in the intestine of LPS-induced septic rats were activated to release NETs, which led to intestinal damage during sepsis. 7 Therefore, it is of great significance to identify ways to improve intestinal barrier function damage during sepsis associated with organ dysfunction and other serious complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] The invasion of additional microbes from the intestine upon the onset of sepsis is another concern that worsens the severity of the patient's condition. [11] Extracorporeal blood treatments, which physically remove inflammationtriggering materials from the blood, have been extensively studied and used in clinical settings as adjuvant therapies for treating bacteremia. [12,13] Conventional extracorporeal blood cleansing devices are mostly based on the adsorption of pathogenic substances to the surface of a scavenging moiety that is coated with specific molecules, such as polymyxin B and heparin, and target endotoxin, bacteria, and cytokines.…”
Section: Introductionmentioning
confidence: 99%